Pengembangan Sistem Informasi Pelanggan Binatu Berbasis Android pada Cleaners VIP Laundry Malang - Andi Moh. Raga Punggawa; Herman Tolle; Lutfi Fanani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Cleaners VIP Laundry is a laundry business operated in Malang which has conventional business process despite it's uncommon service offered such as laundry truck. Based on analysis, there are some issues found related to customer. Lost transaction note, due payments and pickups, difficulties in delivery, wrong address, or utterly not doing delivery. The laundry often take manual solution and rely much on human capabilities such as memory. Cleaners VIP Laundry also exerts on building networks to it's customers. Therefore, the offered solution is to build an Android-based laundry's customer information system which has mobile features along with web-based administration information system on it's sideline. The information system is built under prototyping method. Business process analysis is helped with BPMN. Prototypes are made at design phase to represent the application and evaluated by the stakeholders. The implementation process is done using Android studio and web programming languages. Database is created under MySQL database management system and integrated via webservice under JSON format. On testing phase, two blackbox testing method, validation and usability testing were used. This research produces an informaton system that can be used to reduces issues on Cleaners VIP Laundry Malang.